Specimen Level and Component Level Simulations of Fatigue Crack Growth Behavior under Cyclic Bending - Suresh Kumar R; B N Rao; Velusamy K; Jalaldeen S (Fracture and Structural Integrity)
Power plant piping system subjected to many cyclic loading conditions leads to fatigue loading and thereby crack initiation in the piping system. Demonstrating Leak-Before-Break (LBB) in the design stage itself plays an important role in ensuring the safety of the Sodium-cooled Fast Reactors (SFR) system. The design code guidelines as per RCC MRx A16 in LBB demonstration is conservative in nature. Conducting experiments for each size of the piping systems are expensive and time-consuming. In this paper present, the efforts taken to develop reliable numerical methods to demonstrate Fatigue Crack Growth (FCG). The geometries selected for the FCG analysis include both specimen level as well as full-scale component. The results show that KI estimate for the plate specimen increased with the increase of ‘a/t’ ratio up to 0.6 and then decreases, whereas, in case of the pipe bend, it reduced beyond the ‘a/t’ ratio of 0.4. This early reduction is due to the influence of global compressive stress present ahead of the crack growth. Thus, component level FCG simulation is essential for the accurate demonstration of LBB. FCG simulation has numerically demonstrated with better engineering accuracy for both specimen level as well as component level geometries